Outcomes in Pelvic Organ Prolapse Surgery in Women Using Chronic Antithrombotic Therapy. Issue 6 (November 2017) - High, Rachel; Kavanagh, Alex; Khavari, Rose; Stewart, Julie; Antosh, Danielle D.
Abstract : Introduction: Chronic antithrombotic therapy is common among patients requiring surgery for pelvic organ prolapse because of age and comorbidities. The impact of chronic anticoagulation on postoperative complications in pelvic organ prolapse surgery has not been investigated. This study aims to determine if patients on chronic antithrombotic therapy are at increased risk for postoperative complications. Methods: This retrospective cohort study included women having prolapse surgery from 2012 to 2015, identified by Current Procedural Terminology codes, excluding patients undergoing concomitant major nonurogynecologic procedures. Baseline characteristics were compared and all procedures performed, operative duration, estimated blood loss, and length of hospitalization. Complications (blood transfusion, intensive care unit admission, reoperation, readmission, hematoma, thromboembolic event, and infection) were compared in women on chronic antithrombotic therapy and controls. Logistic regression determined odds ratio (OR) for complications in patients on chronic antithrombotics. Complications were graded by the Clavien-Dindo classification. Results: A total of 388 charts were reviewed, and 386 patients met inclusion criteria. Twenty-one of the 386 patients were on chronic antithrombotic therapy. Chronic antithrombotic therapy increased overall complications (OR, 6.8; P < 0.0005), blood transfusion (OR, 165; P < 0.001), intensive care unit admission (OR, 19.10; P < 0.004), hospital readmission (OR, 20.7; P < 0.0005), vaginal hematoma (OR, 554.1; P < 0.001), infection (OR, 22.44; P < 0.004), and complications that required specific additional follow-up (OR, 9.42; P < 0.0005). There were no thromboembolic events. Antithrombotic therapy did not significantly increase reoperation rates (OR, 3.8; P = 0.275). Findings were maintained when adjusting for covariates of age and body mass index. Conclusions: Postoperative surgical complications after prolapse repair procedures are increased in patients who use chronic antithrombotic medication, the majority of cases are successfully managed conservatively. Abstract : This retrospective cohort study evaluating pelvic organ prolapse surgery patients demonstrates an increased risk of overall postoperative complications, bleeding complications, readmissions, admissions to the intensive care unit, longer hospital stay, and greater estimated blood loss in patients using chronic antithrombotic therapy.